Activation of AMPK Promotes Maturation of Cardiomyocytes Derived From Human Induced Pluripotent Stem Cells - Ye, Liang; Zhang, Xinyuan; Zhou, Qin; Tan, Bin; Xu, Hao; Yi, Qin; Yan, Liang; Xie, Min; Zhang, Yin; Tian, Jie; Zhu, Jing (Frontiers in Cell and Developmental Biology, 2021)
Human induced pluripotent stem cell (iPSC)-derived cardiomyocytes (CMs) (hiPSC-CMs) are a promising cell source for disease modeling, myocardial regeneration, and drug assessment. However, hiPSC-CMs have certain immature fetal CM-like properties that are different from the characteristics of adult CMs in several aspects, including cellular structure, mitochondrial function, and metabolism, thus limiting their applications. Adenosine 5‘-monophosphate (AMP)-activated protein kinase (AMPK) is an energy-sensing protein kinase involved in the regulation of fatty acid oxidation and mitochondrial biogenesis in cardiomyocytes. This study investigated the effects of AMPK on the maturation of hiPSC-CMs. Activation of AMPK in hiPSC-CMs significantly increased the expression of CM-specific markers and resulted in a more mature myocardial structure compared to that in the control cells. We found that activation of AMPK improved mitochondrial oxidative phosphorylation (OxPhos) and the oxygen consumption rate (OCR). Additionally, our data demonstrated that activation of AMPK increased mitochondrial fusion to promote the maturation of mitochondrial structure and function. Overall, activation of AMPK is an effective approach to promote hiPSC-CMs maturation, which may enhance the utility of hiPSC-CMs in clinical applications.